Magnesium Homeostasis and Implications for Human Health: A Review of the Literature - Piotr Marcin Dudziak; Maria Golińska; Mateusz Łyko; Jakub Kurasz; Paweł Siudziński; Wojciech Maj; Alicja Skoczylas; Wiktoria Podlasiewicz; Katarzyna Pala; Anna Nowak (Quality in Sport)
Magnesium ions (Mg²⁺) is a vital ion for human health, involved in numerous bodily functions, including energy production and protein synthesis. Despite its significance, serum magnesium levels are often overlooked in clinical settings, even though they can be disrupted in various health conditions. This review delves into the role of magnesium in human health and disease, highlighting its importance in key organs like the brain, heart, and muscles. Magnesium supplementation has shown promise in treating conditions such as migraine, depression, heart disease, and asthma. Recent discoveries have unveiled genetic factors, including mutations in specific genes, that can lead to magnesium deficiency. Additionally, certain medications, such as diuretics and proton pump inhibitors, can contribute to low magnesium levels. This review explores the mechanisms of magnesium regulation in the intestines, kidneys, and bones.